2010
DOI: 10.12693/aphyspola.117.394
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Ferritin Desorption from Gold Initiated by In Situ pH-Change

Abstract: One of the main questions regarding protein adsorption is about the reversibility of the adsorption process. To get a deeper understanding of this, adsorption of ferritin on Au was studied by quartz crystal microbalance and the pH of the buffer was changed in situ between two values that favour adsorption by different amounts. We found that although some ferritin desorbs from Au, the desorption is incomplete. When the desorption reached a constant value, we returned to the original conditions and investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Poór et al showed with QCM that changing the pH to 7.5 and back to 5.0 by injecting KOH or HCl induces partial desorption and readsorption, respectively, of ferritin adsorbed on gold. Approximately 50% of the initial adsorbed amount was released independently of the initial adsorption time or adsorbed amount . Similarly, the different surface electrostatic potential, hydrophobicity or hydrophilicity, of a freshly chemically etched silicon surface and a silicon oxide pattern can be used for spatially selective ferritin deposition .…”
Section: Fabrication Of Two-dimensional Arrays Of Ferritinmentioning
confidence: 99%
“…Poór et al showed with QCM that changing the pH to 7.5 and back to 5.0 by injecting KOH or HCl induces partial desorption and readsorption, respectively, of ferritin adsorbed on gold. Approximately 50% of the initial adsorbed amount was released independently of the initial adsorption time or adsorbed amount . Similarly, the different surface electrostatic potential, hydrophobicity or hydrophilicity, of a freshly chemically etched silicon surface and a silicon oxide pattern can be used for spatially selective ferritin deposition .…”
Section: Fabrication Of Two-dimensional Arrays Of Ferritinmentioning
confidence: 99%
“…QCM was then used to study amyloid growth and behaviour in real time (Buell et al ., ), allowing a subsequent study of various aspects of amyloid fibril formation (see the section on conformation changes of proteins and protein films below). Factors affecting protein adsorption on gold surfaces were studied, such as protein molecular structure (Nezu et al ., ), surface coating and passivating layers (tyrosine hydroxylase binding to mercaptoundecanoic acid‐coated gold) (Halskau et al ., ); cytochromes b 5 binding to cysteine modified gold (Zhavnerko et al ., )) and the reversibility of protein binding (Poor et al ., ).…”
Section: Protein Interactionsmentioning
confidence: 97%